2020
DOI: 10.2174/1566523220666200916120708
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-146a Improves Immunomodulatory Effects of MSC-derived Exosomes in Rheumatoid Arthritis

Abstract: Background: Rheumatoid arthritis ( RA) is a severe inflammatory joint disorder and several studies have taken note of the probability that microRNAs ( miRNAs) play an important role in RA pathogenesis. MiR-146 and miR-155 arose as primary immune response regulators. Mesenchymal stem cells (MSCs) immunomodulatory function is primarily regulated by paracrine factors, such as exosomes. Exosomes, which serve as carriers of genetic information in cell-to-cell communication, transmit miRNAs between cells and have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 61 publications
0
59
1
Order By: Relevance
“…Rendering the findings by Dey et al that interaction between RAC2 and inducible nitric oxide synthase (iNOS) may provoke NO upregulation and consequently initiate chronic inflammation in the RA synovium, application of therapeutic strategies focusing on RAC2 inhibition can exert beneficial effects in RA patients [219]. Another preclinical study suggested that MSC-derived exosomes with overexpressed miR-146a, a well-known miRNA involved in regulation of immune response, improved FoxP3, TGF-β, and IL-10 gene expression in murine CIA models, proposing their potential for treating RA through enhancing Treg cell populations and anti-inflammatory cytokine levels [220]. According to the promising results based on MSC therapy for RA in animal models, several clinical trials have been accomplished to report the safety and efficacy of these cell transplantation in human models.…”
Section: Mscs In Rheumatoid Arthritismentioning
confidence: 99%
“…Rendering the findings by Dey et al that interaction between RAC2 and inducible nitric oxide synthase (iNOS) may provoke NO upregulation and consequently initiate chronic inflammation in the RA synovium, application of therapeutic strategies focusing on RAC2 inhibition can exert beneficial effects in RA patients [219]. Another preclinical study suggested that MSC-derived exosomes with overexpressed miR-146a, a well-known miRNA involved in regulation of immune response, improved FoxP3, TGF-β, and IL-10 gene expression in murine CIA models, proposing their potential for treating RA through enhancing Treg cell populations and anti-inflammatory cytokine levels [220]. According to the promising results based on MSC therapy for RA in animal models, several clinical trials have been accomplished to report the safety and efficacy of these cell transplantation in human models.…”
Section: Mscs In Rheumatoid Arthritismentioning
confidence: 99%
“…By contrast, miR-146a was the most significantly up-regulated in TNFastimulated human umbilical cord MSCs even though no functional assay confirmed a possible immunosuppressive role (15). Recently, exosomes from MSCs over-expressing miR-146a were demonstrated to increase Treg cell populations and improve collagen-induced arthritis (16). In the present study, we did not observe any effect on the proliferation of T lymphocytes.…”
Section: Discussioncontrasting
confidence: 81%
“…Exosomes release into the extracellular milieu influences cellular morphology by interfering with cell signaling components and by modulating recipient gene expressions and functions and the cell differentiation program. Exosomes have been reported to influence infections [ 91 , 92 , 93 ], tumor development and metastasis [ 94 , 95 , 96 , 97 , 98 ], neurodegenerative diseases [ 99 , 100 , 101 , 102 ], inflammation, and autoimmune disorders [ 103 , 104 , 105 , 106 ]. In addition, they play crucial role in intracellular communication and in the pathogenesis of several diseases as they can transfer signals (cytokines, proteins, lipids, nucleic acids, and infectious agents) from cells to nearby or distant locations [ 91 , 107 , 108 ].…”
Section: Immunomodulatory Effect Of Exosomesmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent stromal cells sourced from bone marrow, adipose tissues, placenta, or umbilical cord ( Table 2 ). Their regenerative capacities underlie their importance in immune modulation [ 106 , 119 , 120 , 121 , 122 ]. The immunomodulatory effects of MSC-derived exosomes on peripheral blood mononuclear cells (PBMCs) have been well established.…”
Section: Immunomodulatory Effect Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation